Microfinance 'plus': The impact of business training on Indian self help groups - Ranjula Bali Swain; Adel Varghese (Uppsala University, Department of Economics, 2010)
The provision of business training with microfinance leads to a positive impact on assets for the participating households. We correct for membership selection bias and account for potential training endogeneity with propensity score matching, using data from the Self Help Group microfinance program in India.
urn:nbn:se:uu:diva-138920
Keywords: G21; I32; O12; 330; India; microfinance; business training; impact studies; Self Help Groups; Mikrofinanzierung; Selbsthilfeförderung (Entwicklungsländer); Wirkungsanalyse; Indien